Incorporating patient‐reported outcomes (PROs) into dialysis policy: Current initiatives, challenges, and opportunities. Issue 1 (20th January 2020) - Umeukeje, Ebele M.; Nair, Devika; Fissell, Rachel B.; Cavanaugh, Kerri L.
Abstract: Governments at national and state levels regulate dialysis care in the United States to ensure safe practices, and continually elevate the quality of care. An objective of these regulatory policies is the independent evaluation of dialysis unit outcomes by patients, caregivers, and the community to facilitate choices as well as to advance equal access to high quality dialysis care. These polices recognized decades ago that it was fundamental to include the patient perspective in the assessment and evaluation of dialysis care quality by requiring both individual and aggregate patient reported outcomes (PROs). Although there is support for integrating the patient perspective, concerns persist about the implementation of these polices including selection of PRO measures, administration timing and reach, as well as interpretation of results including benchmarking to permit comparisons across organizations. The experience from the early adoption of PROs into dialysis policies in conjunction with advances in electronic health records, personal data capture and monitoring, and analytics is poised to address these concerns. The dialysis community has the opportunity to lead the way in innovation related to PRO implementation not only in kidney disease care, but also for other healthcare conditions or contexts such as oncology, surgical, and acute care.